Canadian aging and inactivity study: Spaceflight-inspired exercises during head-down tilt bedrest blunted reductions in muscle-pump but not cardiac baroreflex in older persons - Sadeghian, Farshid; Divsalar, Donya Naz; Fadil, Rabie; Tavakolian, Kouhyar; Blaber, Andrew P. (Frontiers in Physiology, 2022)
As part of the first Canadian aging and inactivity study (CAIS) we assessed the efficacy of space-based exercise countermeasure for maintenance of cardiac and muscle-pump baroreflex in older persons bedrest. An initiative of the Canadian Space Agency, Canadian Institutes of Health Research and the Canadian Frailty Network, CAIS involved 14 days of 6-degree head-down tilt bedrest (HDBR) with (Exercise) or without (Control) combined upper and lower body strength, aerobic, and high-intensity interval training exercise countermeasures. Twenty healthy men and women aged 55 to 65, randomly divided into control and exercise groups (male control (MC, n=5), male exercise (ME, n=5), female control (FC, n=6), female exercise (FE, n=4)) (age: 58.7±0.5 years, height: 1.67±0.02 m, body mass: 70.2±3.2 kg; mean±SEM), completed the study. Cardiac and muscle-pump baroreflex activity were assessed with supine-to-stand tests. Wavelet transform coherence was used to characterise cardiac and muscle-pump baroreflex fraction time active (FTA) and gain values, and convergent cross-mapping was used to investigate causal directionality between blood pressure (BP) and heart rate, as well as BP and lower leg muscle electromyography (EMG). Seven of the twenty participants were unable to stand for six minutes after HDBR, with six of those being female. Our findings showed that two weeks of bedrest differently impaired skeletal muscle's ability to return blood to the venous circulation in various sexes and intervention groups. Comparing values after bed rest with before bed rest values, there was a significant increase in heart rates (∆ of +25%; +17% in MC to +33% in FC; p<0.0001), beat-to-beat EMG decreased (∆ of -43%; 25% in ME to 58% in MC; p<0.02), while BP change was dependent on sex and intervention groups. Unlike their male counterparts, in terms of muscle-pump baroreflex, female participants had considerably decreased FTA after HDBR (p<0.01). All groups except female control demonstrated parallel decreases in cardiac active gain and causality, while the FC demonstrated an increase in cardiac causality despite a similar decline in cardiac active gain. Results showed that the proposed exercises may alleviate muscle-pump baroreflex declines but could not influence the cardiac baroreflex decline from 14 days of inactivity in older adults.